THE USE OF PICTURE MEDIA TO IMPROVE WRITING NARRATIVES OF GRADE V STUDENTS IN INDONESIAN LANGUAGE LEARNING AT MIN BIMA CITY - Nurhaidah, Siti; Syarifuddin, Syarifuddin; Masitha, Dewi (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
This study is motivated by the lack of student interest and motivation, which when examined further through initial observations turned out to be caused by several factors. Generally, researchers found several problems when the learning was taking place. Some students have a delay in responding to the material provided by the teacher, there are some students who have different thinking abilities and interest talents, low absorption and most students do not understand narrating what they think so that it affects their thinking power and are reluctant to try so that it causes laziness in receiving learning and not focusing on what the teacher says. This research is a grade action research conducted in two cycles with the stages of planning, action implementation, observation and reflection. Data collection techniques are observation method, test method, interview method, documentation method. The purpose of this study was to determine the use, ability of writing narratives and the effect of using image media in improving writing narratives of VD grade students in Indonesian language learning subjects at MIN Kita Bima. The results showed that the use of image media can improve writing narratives in students. in this activity, students have been able to write narratives in accordance with the rules of narrative writing. The implementation of learning by using this image media in cycle II is better than in cycle I. The shortcomings in cycle I have been improved in cycle II, namely the allocation of students can increase their imagination so that they can easily narrate their writing well. The use of image media is very suitable and effective to improve the ability of writing narratives for VD grade students at MIN Bima City.